Assessing METland® Design and Performance Through LCA: Techno-Environmental Study With Multifunctional Unit Perspective - Peñacoba-Antona, Lorena; Senán-Salinas, Jorge; Aguirre-Sierra, Arantxa; Letón, Pedro; Salas, Juan José; García-Calvo, Eloy; Esteve-Núñez, Abraham (Frontiers in Microbiology, 2021)
Conventional wastewater treatment technologies are costly and energy demanding; such issues are especially remarkable when small communities have to clean-up their pollutants. In response to these requirements a new variety nature-based solution, so call METland®, has been recently develop by using concepts from Microbial Electrochemical Technologies (MET) to outperform classical constructed wetland regarding wastewater treatment. Thus, the current study evaluates two operation mode (aerobic and aerobic-anoxic) of a full-scale METland®, including a Life Cycle Assessment (LCA) conducted under a Net Environmental Balance perspective. Moreover, a combined technical and environmental analysis using a Net Eutrophication Balance (NEuB) focus concluded that the downflow (aerobic) mode achieved the highest removal rates for both organic pollutant and nitrogen, and it was revealed as the most environmentally friendly design. Actually, aerobic configuration outperformed anaero/aero-mixed mode in a fold-range from 9 to 30%. LCA was indeed recalculated under diverse Functional Units (FU) to determine the influence of each FU in the impacts. Furthermore, in comparison with constructed wetland, METland® showed a remarkable increase in wastewater treatment capacity per surface area (0.6m2/pe) without using external energy. Specifically, these results suggest that aerobic-anoxic configuration could be more environmentally friendly under specific situations where high N removal is required. The removal rates achieved demonstrated a robust adaptation to influent variations, revealing a removal average of 92% of Biology Oxygen Demand (BOD), 90% of Total Suspended Solids (TSS), 40% of total nitrogen (TN) and 30% of total phosphorus (TP). Moreover, regarding the global warming category the overall impact was 75% lower compare to other conventional treatments like activated sludge. In conclusion, the LCA revealed METland® appears as ideal solution for rural areas, considering the low energy requirements and high efficiency to remove organic pollutants, nitrogen, phosphates from urban wastewater.